VORLESUNGEN UBER DIFFERENTIAL - UND INTEGRALRECHNUNG...ZUM GEBRAUCH BEI AKADEMISCHEN VORTRAGEN SOWIE ZUM SELBSTSTUDIUM... - Ostrowski, Alexander (Basel Verlag Birkhauser, 1960)
LECTURES ON DIFFERENTIAL - AND INTEGRAL CALCULATION ... FOR USE IN ACADEMIC LECTURES AS WELL AS IN SELF-STUDY ...
Keywords: Calculus, Differential; Calculus, Integral